X-ray photonics in free-electron-driven van der Waals materials - Tey, Kai Zhong (Nanyang Technological University, 2022)
With the growing interest in highly tunable, high brightness laboratory scaled X-ray sources, a new way to produce X-ray is discovered. Tunable X-ray generation can be carried out with the use of van der Waals materials. This enables experiments like core level spectroscopy can be carried out in normal laboratory instead of undulator facilities. The aim of this project is to create learning tools for year 3-4 university students. This report will serve as a literature review for interested students to understand more about X-ray generation. At the end, a mobile application will be created to assist students to visualise certain key equations regardless of their location.